A Review of Students' Critical Thinking Skills in Science Learning in Indonesia - Arda, Arda; Supriyatman, Supriyatman; Afadil, Afadil (Jurnal Pendidikan MIPA, 2024)
A Review of Students' Critical Thinking Skills in Science Learning in Indonesia. Objective: This review study aims to analyse and describe the development of students' critical thinking skills in science learning. Methods: This study uses a systematic literature review by following the PRISMA form. We found 158 documents critical thinking skills in science learning in published in Scopus indexed journals from 2014 to 2024. After the screening process, 16 articles were selected for analysis using thematic analysis. Findings: The review findings show that the selection of learning media to enhance critical thinking skills in flexible science learning should be aligned with students' characteristics, the learning context and user-friendliness. The choice of learning models employed to improve critical thinking skills in science learning is highly variable and must be tailored to multiple criteria. Selecting the suitable model necessitates consideration of the students' attributes, the educational material, and the time constraints. Every learning model possesses distinct advantages in promoting critical thinking skills, necessitating the selection of the model that most effectively aligns with the particular requirements and educational situation. Conclusion: Critical thinking skills are among the most vital competencies that students should acquire. These skills are crucial in facilitating a deeper comprehension of scientific concepts among students. The literature study indicates that from 2014 to 2024, many media and learning approaches have been extensively utilized in science education. These media and educational approaches have demonstrated a beneficial effect, enhancing students' academic performance while also fostering the optimal development of their critical thinking skills.       Keywords: critical thinking skills, science learning, systematic literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1787-1798